Assimilate the auditory scale with wavelet packet filters for multistyle classification of speech under stress - Nurul Aida Amira, Johari; Muthusamy, Hariharan, Dr.; Saidatul Ardeenawatie, Awang; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/